Spatial intra‐tumour heterogeneity in acquired resistance to targeted therapy complicates the use of PDX models for co‐clinical cancer studies - Claudia Wellbrock (EMBO Molecular Medicine)
Abstract Targeted therapy in the treatment of cancer has produced great clinical successes. However, with these came the challenge of acquired resistance. Melanoma, a cancer that carries one of the highest mutational burdens, displays great complexity in mutational acquired resistance with a notable degree of inter‐tumoural heterogeneity. In this issue of EMBO Molecular Medicine, Kemper et al (2015) describe the identification of multiple, partly novel resistance mechanisms present in one patient and within a single metastasis, where one mutation could be traced back to a pre‐treatment lesion. Importantly, the observed intra‐tumoural “spatial” heterogeneity can impact on the interpretability of patient‐derived xenografts, and this might have implications particularly for co‐clinical treatment studies.